FEATURES OF TRANSFORMATION OF TRADE STRUCTURE IN THE MODERN WORLD MOTOR VEHICLES’ MARKET - A. Pas’Ko (Вестник университета)
At the present stag, in the conditions of toughening of the competition in the world motor vehicles’ market for it there is characteristic not only a complication of trade structure, but also transformation of industry structure. In the article evaluation of the high-quality shifts happening in world automotive industry for the last years is carried out.